Extra-pancreatic solid pseudopapillary neoplasm: a case report of primary testis origin and review of the literature - Lu, Qian; Yang, Liming; Li, Shiyan (Frontiers in Oncology, 2026)
Solid pseudopapillary neoplasm (SPN) is a rare tumor with low malignant potential, generally occurring in the pancreas. In this article, we report a case of extra-pancreatic solid pseudopapillary neoplasm of the testis (ESPN-T) of a 36-year-old male patient. The patient incidentally discovered a scrotal mass. Ultrasonography revealed a well-defined, regular cystic-solid lesion within the left testis. Magnetic resonance imaging (MRI) showed a nodular mass within the left testis, characterized by an isointense signal on T1-weighted imaging, a heterogeneous signal on T2-weighted imaging, and inhomogeneous enhancement after contrast administration. The patient subsequently underwent radical orchiectomy on the left side. The morphologic and immunohistochemical features of the testicular lesion confirmed the diagnosis of ESPN. Follow-up for 2 years after surgery revealed no signs of recurrence or metastasis. This is a rare case of SPN in the testis in China, which expands the differential diagnosis of testicular lesions and therapeutic strategies of ESPNs.